Water-soluble organic carbon in snow and ice deposited at Alpine, Greenland, and Antarctic sites: a critical review of available data and their atmospheric relevance - M. Legrand; S. Preunkert; B. Jourdain; J. Guilhermet; X. Faïn; I. Alekhina; J. R. Petit (Climate of the Past, 2013)
While it is now recognized that organic matter dominates the present-day atmospheric aerosol load over continents, its sources remain poorly known. The studies of organic species or organic fractions trapped in ice cores may help to overcome this lack of knowledge. Available data on the dissolved (or total) organic carbon (DOC or TOC) content of snow and ice often appear largely inconsistent, and, until now, no critical review has been conducted to understand the causes of these inconsistencies. To draw a more consistent picture of the organic carbon amount present in solid precipitation that accumulates on cold glaciers, we here review available data and, when needed, complete the data set with analyses of selected samples. The different data sets are then discussed by considering the age (modern versus pre-industrial, Holocene versus Last glacial Maximum) and type (surface snow, firn, or ice) of investigated samples, the deployed method, and the applied contamination control. Finally, the OC (DOC or TOC) levels of Antarctic, Greenland, and Alpine ice cores are compared and discussed with respect to natural (biomass burning, vegetation emissions) and anthropogenic sources (fossil fuel combustion) contributing to atmospheric OC aerosol.